PERIODS OF PSYCHOLOGICAL CHANGES IN THE MIND OF YOUNG PEOPLE - Khojayeva Nozima Kadamboyevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: This article talks about the psychological types and periods of age. Age is an integral characteristic of a person, which reflects the life span of a person and the level of development achieved as a result of life.